THE SUPRA-LONG SCOTS PINE TREE-RING RECORD FOR FINNISH LAPLAND: PART 2, INTERANNUAL TO CENTENNIAL VARIABILITY IN SUMMER TEMPERATURES FOR 7500 YEARS - Helama S.; Lindholm M.; Eronen M.; Timonen M.; Meriläinen J. (My University, 2002)
Midsummer (July) temperatures are reconstructed for the last 7500 years using the long ring-width chronology of Scots pine (Pinus sylvestris L.) from northern Finland. The chronology was built using regional curve standardization (RCS), which allows for long-term (low-frequency) variability to be extracted from this annually resolved record of 1087 samples from living trees and subfossil timber. Short-and long-term changes in reconstructed July temperatures are presented. The regression model accounts for 37% of the dependent instrumental temperature variance between ad 1879 and 1992. The warmest 30-year periods were ad 560–531, ad 560–531, 1190–1161 bc and ad 1541–1570, and the coldest 5240–5211, 5150–5121 and 3710–3681 bc. The warmest 100-year periods were ad 1501–1600, 600–501 bc and 300–201 bc, and the coldest 5200–5101, 2500–2401 and 1500–1401 bc. Broad comparisons are made with dendrochronological, lacustrine and glacial proxy evidence.
Keywords: Dendroclimatology; tree rings; summer temperature; Pinus sylvestris; Finnish Lapland; Holocene